Blocking of TRPV-1 in the parodontium relieves orthodontic pain by inhibiting the expression of TRPV-1 in the trigeminal ganglion during experimental tooth movement in rats. (15th August 2016) - Gao, Yunan; Liu, Yingfei; Zhu, Kun; Zhang, Zhichao; Qiao, Hu; Lu, Zhen; Zhong, Tianyu; Liu, Yong; Zhou, Hong
Highlights: Experimental tooth movement increases the expression of TRPV1 in the parodontium. TRPV1 activation in the parodontium increases the expression of TRPV1 in the trigeminal ganglion. TRPV1 blockade in the parodontium decreases orthodontic pain by reducing the expression of TRPV1 in the trigeminal ganglion. Abstract: Orthodontic pain has confused the orthodontics for a long time, and recent research demonstrated that transient receptor potential vanilloid type 1 (TRPV1) had crucial functions in transduction of painful stimuli. The present research investigated the analgesia effects of the blocking TRPV1 on orthodontic pain during experimental tooth movement. Under challenge with experimental tooth movement, the expression of TRPV1 in the parodontium was increased in a time-dependent and force-dependent manner. And treatment with selective TRPV1 antagonist AMG-9810 in the parodontium reduced the expression of TRPV1 in the trigeminal ganglion (TG) and decreased the secretion of IL-1β in the gingival crevicular fluid. Furthermore, AMG-9810 could relieve orthodontic pain arising from experimental tooth movement in rats. We suggest that TRPV1 both in the parodontium and trigeminal ganglion are involved in orthodontic pain, and TRPV1 in the parodontium influence on orthodontic pain through reducing the expression of TRPV1 in trigeminal ganglion. Our finding may help to develop strategies for relieving orthodontic pain after orthodontics.